A General Chemoenzymatic Strategy for the Synthesis of Glycosphingolipids. Issue 25 (16th August 2016) - Liu, Yunpeng; Wen, Liuqing; Li, Lei; Gadi, Madhusudhan Reddy; Guan, Wanyi; Huang, Kenneth; Xiao, Zhongying; Wei, Mohui; Ma, Cheng; Zhang, Qing; Yu, Hai; Chen, Xi; et al.
Abstract : A concise, prototypical, and stereoselective strategy for the synthesis of therapeutically and immunologically significant glycosphingolipids has been developed. This strategy provides a universal platform for glycosphingolipid synthesis by block coupling of enzymatically prepared free oligosaccharideglycans to lipids using glycosyl N ‐phenyltrifluoroacetimidates as efficient activated intermediates. As demonstrated here, two different types of glycosphingolipids were obtained in excellent yields using the method. Abstract : Firstly, three oligosaccharides were prepared by a one‐pot multienzyme system (OPME). Subsequently, the oligosaccharides were easily converted to N ‐phenyltrifluoroacetimidate donors using benzoyl as protecting group, followed by block coupling of enzymatically prepared sugar parts to lipid acceptors with TMSOTf as a promotor to produce corresponding GSLs.